Rifampin: Inhibition of Ribonucleic Acid Synthesis After Potentiation by Amphotericin B in Saccharomyces cerevisiae - Battaner, E. (1974)
The inhibition of Saccharomyces cerevisiae growth by amphotericin B and rifampin was studied. Rifampin alone had no effect on growth or macromolecular syntheses. Lethal amounts of amphotericin B produced a late inhibition of ribonucleic acid (RNA) synthesis simultaneous with the arrest of growth and protein synthesis. In contrast, low doses of amphotericin B along with rifampin caused an early arrest of RNA synthesis, followed by a later arrest of growth and protein synthesis. Used with rifampin, amphotericin B thus appears to increase cell permeability for rifampin, which in turn inhibits RNA synthesis; such results are consistent with some reports of inhibition of yeast RNA polymerase function by rifampin. Experiments with petite mutants ruled out any special effect of the antibiotics on mitochondrial RNA synthesis, so that nuclear RNA synthesis is affected. Acrylamide gel analyses of RNA pulse-labeled after addition of the two antibiotics in synergy showed that synthesis of all major classes of RNA was progressively and uniformly inhibited.